The Role Of Dream In Reviving The Religious Awareness InDickens's Novel A Christmas Carol And Other Holiday Treasures (1843): A Jungian Analytic Psychology - PURNAMASARI, IDA (2016)
ABSTRACT This research aims to analyze Scrooge's religious awareness dynamics based on Charles Dickens' A Christmas Carol and Other Holiday Treasures, to assert the efforts that have done by the people around Scrooge in reviving Scrooge's religious awareness, and to reveal the role of dream in reviving Scrooge from his consideration that Christmas is useless and there is nothing to be merry at Christmas by means of Jungian Analytic Psychology. The type of this research is descriptive qualitative. The researcher gets the data from the novel includes the narration, monologue, and dialogue. The techniques of collecting the data are reading the data repeatedly, taking notes, underlying the important words, arranging the data, selecting the data, and drawing conclusion. The technique of data analysis is descriptive interactive which comprises three procedures, namely: data reduction, data display, and conclusion. The results of this research show: 1) the Scrooge's religious dynamics starts with unguided faith, lost of faith and regained faith. 2) the efforts of the people around Scrooge in reviving Scrooge's religious awareness are provided by Scrooge's nephew, Scrooge's girlfriend, and Jacob Marley. 3) the role of dream in reviving Scrooge's religious awareness are dream as reminder, dream as enlightenment, and dream as foreseeing. Keyword: dream, spirit, religious awareness, Jungian analytic psychology, Christmas carol ABSTRACT This research aims to analyze Scrooge's religious awareness dynamics based on Charles Dickens' A Christmas Carol and Other Holiday Treasures, to assert the efforts that have done by the people around Scrooge in reviving Scrooge's religious awareness, and to reveal the role of dream in reviving Scrooge from his consideration that Christmas is useless and there is nothing to be merry at Christmas by means of Jungian Analytic Psychology. The type of this research is descriptive qualitative. The researcher gets the data from the novel includes the narration, monologue, and dialogue. The techniques of collecting the data are reading the data repeatedly, taking notes, underlying the important words, arranging the data, selecting the data, and drawing conclusion. The technique of data analysis is descriptive interactive which comprises three procedures, namely: data reduction, data display, and conclusion. The results of this research show: 1) the Scrooge's religious dynamics starts with unguided faith, lost of faith and regained faith. 2) the efforts of the people around Scrooge in reviving Scrooge's religious awareness are provided by Scrooge's nephew, Scrooge's girlfriend, and Jacob Marley. 3) the role of dream in reviving Scrooge's religious awareness are dream as reminder, dream as enlightenment, and dream as foreseeing. Keyword: dream, spirit, religious awareness, Jungian analytic psychology, Christmas carol